Contralateral breast metastasis from pulmonary adenocarcinoma: Two cases report and literature review - Ji, Fang-Fang; Gao, Peng; Wang, Ji-Gang; Zhao, Jie; Zhao, Peng (Journal of Thoracic Disease, 2012)
Carcinoma metastatic to breast from extra-mammary malignancy is rare and only accounts for 0.4-1.3% of all breast cancer. Two rare cases of single breast metastasis from pulmonary adenocarcinoma were reported here with a brief review of the pertinent literature. The only complaint of the these two female patients was painless breast mass found recently. Most breast metastasis previously reported are present in the upper outer quadrant, however, in our study, one case was found to be located in the lower inner quadrant and the other in the upper inner quadrant. Tumor cells from breast biopsy were immune-positive for thyroid transcription factor-1. The two patients survived 5 and 8 months, respectively, following the diagnosis of both the primary lung tumor and the breast metastasis. Breast metastasis from lung adenocarcinoma is rare but does exist. The awareness of this possibility may help to differentiate the tumor from primary breast carcinoma. Clinical history and immunohistochemical studies are essential to reach the final diagnosis.